Chronic Kidney Disease: A Case Series (Part 4) (Advancements in Homeopathic Research, 2024)
Gupta et. al. in their previous three publications(1-4) demonstrated that not only patients of chronic renal  failure (CRF) can be improved by homoeopathic  treatment, along with change in life style, strict diet  and regimen, but also the patients of acute renal failure  (ARF) can be prevented from further deterioration.  Gupta et. al. published two series of 3 cases each on  successful management of CRF(2,3) by homoeopathic  remedies avoiding dialysis and renal transplant. The  third case series is on management of acute renal  failure (ARF)(4) by homoeopathic medicines. This  fourth case series is on successful management of  CRF patients by maintaining their serum creatinine  level and eGFR within a reasonable range, preventing  further deterioration and improving their quality of  life for a considerable period of time. The first case  in this series is of an anaemic, hypertensive, diabetic  male with CKD with reduction in S. Urea and  Creatinine level followed for 2 years and 9 months.  The second case is of a 52-year old hypertensive  female and third case is of a 71-year old hypertensive  male with maintained S. Urea and Creatinine level  without haemodialysis for more than 1 year. In all the  3 cases, repeated renal function test and eGFR(5) was  the main parameter to assess the functional status of  kidney and response to homoeopathic treatment.
Keywords: Haemodialysis (HD); peritoneal dialysis (PD); chronic kidney disease (CKD); chronic renal failure (CRF); end stage renal disease (ESRD); serum urea; blood urea nitrogen (BUN); serum creatinine; estimated glomerular filtration rate (eGFR); renal transplant; homoeopathic treatment.